2015
DOI: 10.1016/j.ebiom.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Double Blind, Placebo-Controlled Pilot Study of Oral Artesunate Therapy for Colorectal Cancer

Abstract: BackgroundArtesunate is an antimalarial agent with broad anti-cancer activity in in vitro and animal experiments and case reports. Artesunate has not been studied in rigorous clinical trials for anticancer effects.AimTo determine the anticancer effect and tolerability of oral artesunate in colorectal cancer (CRC).MethodsThis was a single centre, randomised, double-blind, placebo-controlled trial. Patients planned for curative resection of biopsy confirmed single primary site CRC were randomised (n = 23) by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 35 publications
1
99
0
9
Order By: Relevance
“…The role of artesunate as an effective anticancer drug is under active examination in phase I–II clinical trials [43], [44]. The selective killing of cancer cells but not normal cells may be the major advantage of artesunate, which is already known to be generally safe and well tolerated, even in the fetus during first-trimester pregnancies [45].…”
Section: Discussionmentioning
confidence: 99%
“…The role of artesunate as an effective anticancer drug is under active examination in phase I–II clinical trials [43], [44]. The selective killing of cancer cells but not normal cells may be the major advantage of artesunate, which is already known to be generally safe and well tolerated, even in the fetus during first-trimester pregnancies [45].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials indicated that the tumor suppression action of ART on advanced breast cancer, 14) colorectal cancer 15) and pancreatic cancer cells. 16) ART increasingly attracts the attention of cancer researchers due to a broad range of anti-cancer activity, such as pro-apoptosis attenuation of tumor growth, metastasis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the combined effects of artesunate and rituximab on malignant B-cells were reported [12]. Clinical pilot phase I/II trials in veterinary tumors and human cancer patients demonstrated that the artemisinin derivative artesunate possesses clinical anticancer activity at tolerable side effects [13,14,15]. It can be speculated that not only artemisinin-type drugs, but also other endoperoxides may reveal anticancer activity.…”
Section: Introductionmentioning
confidence: 99%